Politisering av religion i norske kommuner? En undersøkelse av religionens rolle i lokale feiringer - Botvar, Pål Ketil (Politik, 2014)
In this article I will take a look at how local municipalities deal with religion when the topic is brought up in local politics. e development towards a multicultural society leads to religion having a more prominent place in the public sphere. During the last 10 years religion has become a theme in public policy at the local level. Such examples are the provision of special rooms or buildings for religious groups to have their ceremo- nies. School children visiting church sermons during school hours is another issue that leads to controversies. In this article I will focus on how representatives for the local community deal with topics related to religion in local festivities and celebrations. e data material relates to how municipalities organize the national day celebration and interact with civil society actors in the preparation of this celebration.